An improved scheme for temperature calculations in food - Ansari, F.A.; Wan, M.A.; Abbas, K.A. (2003)
In an earlier paper, an empirical approach was reported to calculate the surface film conductance during cooling of slab shaped fish pieces. It was demonstrated there that when this surface film conductance value was used for temperature calculations, improved results were obtained. During repeated calculations, surface film conductance values were found to be a function of temperature. A correlation was developed for variable film conductance, and this correlation was used instead of a constant value. This resulted in an excellent agreement between the calculated and measured temperatures. © 2002 Elsevier Science Ltd. All rights reserved.